Extent of lung involvement by tomography in patients with SARS-CoV-2 pneumonia - Collins, Jaime A. (2021)
Objective. To determine the extent of pulmonary involvement in patients with SARS-CoV-2 pneumonia usingtomography. Method. Retrospective evaluation in patients with evidence of COVID-19 at the Guillermo Almenara Irigoyen National Hospital, Lima - Peru, at the beginning of the COVID-19 pandemic, between March 15 and May 14, 2020. The extent of pneumonia was determined by means of tomography based on the Classification of the French Society of Thoracic Imaging. Results. 485 patients were included in the study. The extent of pneumonia was: 1.2% absent, 4.9% minimal, 20.6% moderate, 27.4% extensive, 30.7% severe, and 15.1% critical. Lung involvement was associated with age older than 60 years (p = 0.014) andambient oxygen saturation below 90% (n = 372, p = 0.000). Conclusions. Due to its extension, the SARSCoV-2 pneumonia in the first two months of the COVID-19 epidemic at Hospital Almenara were severe, extensive and mostly moderate. The extent of pneumonia was associated with age and ambient oxygen saturation at admission.